Hereditary Hyperferritinemia Cataract Syndrome: Clinical, Genetic, and Laboratory Findings in 5 Families - Nonnenmacher, L.; Langer, T.; Blessing, H.; Gabriel, H.; Buchwald, H.-J.; Meneksedag, C.; Kohne, E.; Gencik, M.; Debatin, K.-M.; Cario, H. (Klinische Pädiatrie, 2011)
The hereditary hyperferritinemia cataract syndrome (HHCS) is an autosomal dominant disorder characterized by high serum ferritin and early onset cataract. Mutations in the iron responsive element (IRE) within the 5´untranslated region of the L-ferritin (FTL) gene lead to constitutive L-ferritin synthesis resulting in hyperferritinemia. Bilateral cataract formation is caused by the intracellular accumulation of ferritin in the lens.4 children from unrelated families were referred for further exploration of hyperferritinemia which was detected during the diagnostic work-up of gastroenterological or hematological disorders. 1 patient was primarily referred for the investigation of bilateral cataract.Diagnostics included routine blood analysis, including complete blood count, iron status, liver and kidney parameters, a physical and an ophthalmological examination. Molecular genetic analysis of the FTL IRE was performed in 4 patients by PCR from genomic DNA and subsequent direct sequencing.All index patients presented with isolated hyperferritinemia without iron overload and had a positive family history for early onset cataract. Age at onset and disease severity varied between different families and among family members. Molecular genetic analysis revealed point mutations within the FTL IRE.In patients with hyperferritinemia but without any other sign of iron overload or inflammation HHCS should be considered to avoid complex and invasive procedures. Vice versa, in patients with familial inherited cataract the early serum ferritin measurement helps to avoid unnecessary diagnostics.
Keywords: hereditary hyperferritinemia cataract syndrome; FTL gene; early onset cataract; hyperferritinemia; HHCS